Macrofungi of Küre Mountains National Park in Bartın region of Turkey - Özkazanç, Nuri Kaan; Keleş, Yağmur Yeşilbaş; Keleş, Yağmur Yeşilbaş; Özkazanç, Nuri Kaan (My University, 2019)
In this study, Küre Mountains National Park, Bartin Province in the rest of the border must macrofungi flora areas and buffer zones between the years 2013 to 2015 inclusive were searched. The results of the field work space Macrofungal 284 samples were collected. A total of 284 macrofungi samples were collected. Laboratory analysis identified 68 species within 11 orders and 29 families. Of these, 3 taxa belong to Ascomycota, and 65 to Basidiomycota. Determined taxa were found to be growing on four types of substrates: 51 from soil, 11 from branches or trunks, 4 from logs, and 2 from leaves. This study can lay the groundwork for further biodiversity studies in the area, providing a basis for ensuring the continuity of the macromycota flora and biological diversity within the national park.
Keywords: Mantar Bilimi